Sustainability of community-based women’s groups: reflections from a participatory intervention for newborn and maternal health in Nepal - Sondaal, Annemijn E C (Community Dev J, 2019)
Participatory community-based women’s group interventions have been successful in improving maternal and newborn survival. In rural Makwanpur, Nepal, exposure to these Participatory Learning and Action groups resulted in a thirty-percent reduction in neonatal mortality rate and significantly fewer maternal deaths. It is often theorised that participatory approaches are more likely to be sustained than top-down approaches, but this is rarely evaluated after the withdrawal of external support. We sought to understand how participatory learning and action (PLA) groups in Makwanpur fared after the supporting non-governmental organisation withdrew their support as well as factors affecting their sustainability. We used mixed methods, conducting a cross-sectional survey of 239 groups, thirty focus group discussions with group members and thirty key informant interviews within twelve–seventeen months after support was withdrawn. Eighty percent of groups were still active which suggests that PLA groups have a high chance of being sustained over time. Groups were more likely to be sustained if the group had local importance and members continued to acquire new knowledge. However, the participatory nature of the group and local embeddedness were not enough to sustain all groups. They also needed leadership capacity, a unifying activity such as a fund, and a strong belief in the value of their meeting to sustain. These key factors should be considered when seeking to enable sustainability of participatory interventions.